ASIO and the Monitoring of Irish Republicans in Australia during the "Troubles". (12th July 2020) - Smith, Evan; Dukova, Anastasia
Abstract : After the "Troubles" broke out in Northern Ireland in 1969, the Australian government became increasingly concerned that these international tensions would manifest themselves within the Irish diaspora. Sympathy for Irish Republicanism was identified in a number of nationalist and socialist groups in Australia which were monitored by the Australian Security Intelligence Organisation (ASIO). Although chiefly focused on the Communist Party of Australia, ASIO monitored Irish Republicans alongside other left‐wing groups and social movements. Based on recently released ASIO files, this article explores the extent to which they were surveilled. The article argues that the monitoring of the Irish Republicans can fit into two periods. The first period, from the outbreak of the "Troubles" in 1969 to 1972, was when Irish Republicanism was seen as an extension of the Communist and Trotskyist groups in Australia. The second period, from 1972 through to the late 1970s, saw security services much more concerned about Irish Republicanism as terrorism, as international terrorism and the expansion of the IRA's bombing campaigns outside of Northern Ireland became an increasing concern. This shift in perceptions of Irish Republicanism demonstrates a wider shift in focus for ASIO and the Australian authorities from Cold War counter‐subversion to counter‐terrorism.